Travel-associated outbreak of COVID-19 in a departmental store, Wenzhou, China - Yiwei Zhou; Fanglv Xiang; Chaorong Ni; Xiaoming Zhang; Haibin Xie; Haishen Zhu; Zumu Zhou (Journal of Infection in Developing Countries)
Introduction: A local outbreak of coronavirus disease 2019 (COVID-19) has rapidly evolved into a global pandemic and the number of cases and deaths has increased exponentially. In this study, we report a COVID-19 outbreak that occurred in a departmental store, between January and February 2020, in Wenzhou, China and investigated the reasons for the outbreak.